Eksistensi Perilaku Lgbt Akibat Penayangan Drama Boys Love Dalam Sudut Pandang Teori Psikoseksual - Tauzia Harari; Ati Kusmawati; Nabila Ayu Dzuhri Rahmah; Febriyani Mufidatul Adha (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
One of the most powerful weapons from the LGBT group today is the drama - drama and film - film they produce, this research is to provide a new view, of how the boys love play can affect the existence of the LGBT group in our midst - and how psychosexual theory views the phenomenon, whether it becomes a basis for a person's sexual orientation to be lesbian, Gay or bisexual. The methods used were qualitative research and literary studies. This approach was chosen because researchers want to explain or describe in detail the phenomena occurring in society, in this case the thought structure experienced by audiences in the drama "boys love". Psychosexual theories view that the concept of self and the direction of sexual orientation of a person is formed from the early stages of childhood development - childhood, at which stage a person is strongly affected by the concept of oneself regarding the direction of sexual orientation. In the future, so, all of the psychosexual processes that have been undergone by those confused looking for sexual orientation, have finally found justification because of the compulsion of psychosocial narcissism themselves.